The popularity of jazz—an unpopular problem: the significance of 'Swing when you're winning' - Parsonage, Catherine (Jazz Research Journal, 2004)
Jazz has entered the academy through the efforts of its supporters to establish it as an important art form in its own right, and as a result, jazz has received academic attention as a field of study largely separate from both contemporary musicology or popular music studies. Interestingly, just as in the classical sphere, the history of jazz has been written, its ‘great’ performers and composers documented and its ‘works’ canonised, and recently these processes have been subject to criticism in a similar way to work undertaken by ‘new’ musicologists. Whilst this ‘high art’ reading of the music is more compatible with conventional scholarly activity and has ensured that jazz has become a valid subject for study at educational institutions, such activity has not always emphasised its popular origins that might undermine its status as an academic discipline. Jazz has remained a specific and marginalized area within contemporary music scholarship, although with a history that spans the period, it has played an integral and influential part in the evolution of music in the modern world,particularly multifarious popular forms. With this in mind, it is ironic that jazz has been largely excluded from serious consideration in popular music studies, a situation due in part to the current trends in research in this field. The focus on recent popular music has led to the approach to research where one work, be it a song or an album, is analysed in detail in terms of its musical structure and within its sociological context, but where consideration of its musical-historical context is often lacking, or is at best perfunctory. The incorporation of a range of popular musics, including pre-rock forms such as jazz, into the popular music studies arena can provide valuable historical and evolutionary perspectives on other more recent developments. In addition, the musical material that is the subject of academic discussion and debate in jazz and popular music studies is often not actually very popular. This neglect of the popular was addressed by Robert Walser, who, at the Leeds International Jazz Education Conference in 2002, argued convincingly for the study of Kenny G alongside Louis Armstrong, Duke Ellington and other well-known jazz musicians. Walser explained that although Kenny G would be seen as abhorrent to many jazz fans due to his technical style of playing, his race and his financial gains from music, the undoubted fact of his massive success means that the academic establishment should not merely ignore him. Rather, there is an argument that Kenny G’s popularity should be examined as a priority.